Phase Behavior Of Co2 And Ch4 Hydrate In Porous Media - Seong-Pil Kang; Ho-Jung Ryu; Yongwon Seo (Zenodo, 2007)
Hydrate phase equilibria for the binary CO2+water and CH4+water mixtures in silica gel pore of nominal diameters 6, 30, and 100 nm were measured and compared with the calculated results based on van der Waals and Platteeuw model. At a specific temperature, three-phase hydrate-water-vapor (HLV) equilibrium curves for pore hydrates were shifted to the higher-pressure condition depending on pore sizes when compared with those of bulk hydrates. Notably, hydrate phase equilibria for the case of 100 nominal nm pore size were nearly identical with those of bulk hydrates. The activities of water in porous silica gels were modified to account for capillary effect, and the calculation results were generally in good agreement with the experimental data. The structural characteristics of gas hydrates in silica gel pores were investigated through NMR spectroscopy. : {"references": ["E. D. Sloan, Clathrate Hydrates of Natural Gas, 2nd ed., New York:\nDekker, 1998.", "H. Teng, A. Yamasaki, M.-K. Chun, and H. Lee, \"Why does CO2 hydrate\ndisposed of in the ocean in the hydrate-formation region dissolve in\nseawater?,\" Energy, vol. 22, no. 12, pp1111-1117, 1997.", "Y. P. Handa, and D. Stupin, \"Thermodynamic properties and dissociation\ncharacteristics of methane and propane hydrates in 70-\u00c5-radius silica gel\npores,\" J. Phys. Chem., vol. 96, no. 21, pp8599-8603, 1992.", "T. Uchida, T. Ebinuma, and T. Ishizaki, \"Dissociation condition\nmeasurements of methane hydrate in confined small pores of porous\nglass,\" J. Phys. Chem. B, vol. 103, no. 18, pp3659-3662, 1999.", "T. Uchida, T. Ebinuma, S. Takeya, J. Nagao, and H. Narita, \"Effects of\npore sizes on dissociation temperatures and pressures of methane, carbon\ndioxide, and propane hydrates in porous media,\" J. Phys. Chem. B, vol.\n106, no. 4, pp820-826, 2002.", "J. W. Wilder, K. Seshadri, and D. H. Smith, \"Modeling hydrate formation\nin media with broad pore size distribution,\" Langmuir, vol. 17, no. 21,\npp6729-6735, 2001.", "J. W. Wilder, K. Seshadri, and D. H. Smith, \"Resolving apparent\ncontradictions in equilibrium measurements for clathrate hydrates in\nporous media,\" J. Phys. Chem. B, vol. 105, no. 41, pp9970-9972, 2001.", "K. Seshadri, J. W. Wilder, and D. H. Smith, \"Measurements of\nequilibrium pressures and temperatures for propane hydrate in silica gels\nwith different pore-size distributions,\" J. Phys. Chem. B, vol. 105, no. 13,\npp2627-2631, 2001.", "D. H. Smith, J. W. Wilder, and K. Seshadri, \"Methane hydrate equilibria\nin silica gels with broad pore-size distributions,\" AIChE J., vol. 48, no. 2,\npp393-400, 2002.\n[10] W. Zhang, J. W. Wilder, and D. H. Smith, \"Interpretation of ethane\nhydrate equilibrium data for porous media involving hydrate-ice\nequilibria,\" AIChE J., vol. 48, no. 10, pp2324-2331, 2002.\n[11] P. Henry, M. Thomas, and M. B. Clennell, \"Formation of natural gas\nhydrates in marine sediments 2. Thermodynamic calculations of stability\nconditions in porous sediments,\" J. Geophys. Res. B, vol. 104, no. B10,\npp23005-23022, 1999.\n[12] M. A. Clarke, M. Pooladi-Darvish, and P. R. Bishnoi, \"A method to\npredict equilibrium conditions of gas hydrate formation in porous media,\"\nInd. Eng. Chem. Res., vol. 38, no. 6, pp2485-2490, 1999.\n[13] Y.-T. Seo, I. L. Moudrakovski, J. A. Ripmeester, J.-W. Lee, and H. Lee,\n\"Efficient recovery of CO2 from flue gas by clathrate hydrate formation in\nporous silica gels,\" Environ. Sci. Technol., vol. 39, no. 7, pp2315-2319,\n2005.\n[14] R. Anderson, M. Llamedo, B. Tohidi, and R. W. Burgass, \"Characteristics\nof clathrate hydrate equilibria in mesopores and interpretation of\nexperimental data,\" J. Phys. Chem. B, vol. 107, no. 15, pp3500-3506,\n2003.\n[15] V. McKoy and O. Sinanoglu, \"Theory of dissociation pressures of some\ngas hydrates,\" J. Chem. Phys., vol. 38, no. 12, pp2946-2956, 1963.\n[16] G. D. Holder, G. Corbin, and K. D. Papadopoulos, \"Thermodynamic and\nmolecular properties of gas hydrates from mixtures containing methane,\nargon, and krypton,\" Ind. Eng. Chem. Fund., vol. 19, no. 3, pp282-286,\n1980.\n[17] R. Anderson, M. Llamedo, B. Tohidi, and R. W. Burgass, \"Experimental\nmeasurement of methane and carbon dioxide clathrate hydrate equilibria\nin mesoporous silica,\" J. Phys. Chem. B, vol. 107, no. 15, pp3507-3514,\n2003.\n[18] Y. Seo, H. Lee, and T. Uchida, \"Methane and carbon dioxide hydrate\nphase behavior in small porous silica gels: three-phase equilibrium\ndetermination and thermodynamic modeling,\" Langmuir, vol. 18, no. 24,\npp9164-9170, 2002.\n[19] Y. Seo and H. Lee, \"A new hydrate-based recovery process for removing\nchlorinated hydrocarbons from aqueous solutions,\" Environ. Sci. Technol.,\nvol. 35, no. 16, pp3386-3390, 2001.\n[20] S.-P. Kang and H. Lee, \"Recovery of CO2 from flue gas using gas hydrate:\nthermodynamic verification through phase equilibrium measurements,\"\nEnviron. Sci. Technol., vol. 34, no. 20, pp4397-4400, 2000."]}